Tropospheric ozone sensing with a differential absorption lidar based on a single CO2 Raman cell - G. Fan; Y. Fu; J. Huo; Y. Xiang; T. Zhang; T. Zhang; W. Liu; Z. Ning (Atmospheric Measurement Techniques)
This study presents the development and performance evaluation of an ozone differential absorption lidar system. The system could effectively obtain vertical profiles of lower-tropospheric ozone in an altitude range of 0.3 to 4 km with high spatiotemporal resolutions. The system emits three laser beams at wavelengths of 276, 287 and 299 nm by using the stimulated Raman effect of carbon dioxide (CO2). A 250 mm telescope and a grating spectrometer are used to collect and separate the backscattering signals at the three wavelengths. Considering the influences of aerosol interference and statistical error, a wavelength pair of 276–287 nm is used for the altitude below 600 m and a wavelength pair of 287–299 nm is used for the altitude above 600 m to invert ozone concentration. We also evaluated the errors caused by the uncertainty of the wavelength index. The developed ozone lidar was deployed in a field campaign that was conducted to measure the vertical profiles of ozone using a tethered balloon platform. The lidar observations agree very well with those of the tethered balloon platform.